Biomolecule protective, antioxygenic and anxiolytic properties of Piper betel leaves extract - S.N.Harsha; K.R. Anilakumar; N. Ilaiyaraja (International Journal of Phytomedicine, 2012)
Piper betel L. is the leaf of a vine belonging to the Piperaceae family. This study was aimed at investigating the biomolecule protective, in vitro antioxidant and anti-anxiety properties. The hydroalcohol extract was examined for radical scavenging ability against 2, 2-diphenyl-2-picryl hydrazyl (DPPH), 2, 2'-azino-bis 3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radicals, metal cheating inhibition, DNA and protein damage protection assay, anti lipid peroxidation, reducing power and nitric oxide radical scavenging activities. The tests employed for anti-anxiety property are open field test (OFT) and elevated plus maze test (EPM) conducted in mice. The IC50 values for metal chelating power, ABTS radical scavenging, NO scavenging and in vitro lipid peroxidation were 272.3µg ml-1,343.3µg ml-1, 309.1µg ml-1 and 146.3µg ml-1 respectively. The plant extract provided protection against DNA and protein damage and this was comparable to gallic acid, the standard. The animals receiving the extracts also showed an increase in the time of stay and number of entries in the open arm of the EPM with increased time mobile in the OFT. The study suggests that the extract of Piper betel possesses antioxidant and anti-anxiety properties, providing significant protection against oxidative damage to major biomolecules.